The psychometric properties of the Arabic version of the fear of COVID-19 scale - Reem Al Khalifah; Afnan Younis; Hessah I Al Suwaidan; Noor AlAnazi; Leena R Baghdadi (Wolters Kluwer Medknow Publications, 2023)
Aim: We aimed to translate and perform transcultural adaptation of the English version of the Fear of COVID-19 Scale (FCV-19S) to Arabic, and assess predictors of COVID-19 fear. Methods: We translated the original seven-item English FCV-19S to Arabic, then back-translated the scale to English. The scale was evaluated by a group of medical experts and participants from the general population to test for content and face validity. The final version of the scale was assessed in a cross-sectional study that included adults residing in Saudi Arabia, who participated in a study to assess the impact of COVID-19 fear on children's vaccination during the COVID-19 pandemic curfew March 24-July 6, 2020. Results: Overall, 577 participants responded to the survey. The mean age was 32.6 ± 5.7 years, and the majority had bachelor's or postgraduate university degrees. COVID-19 was diagnosed in 1.4% of the participants. The mean total score for the COVID-19 fear scale was 20 ± 5.4. The COVID-19 fear scale had excellent internal consistency and Cronbach's alpha 0.85 (95% confidence interval 0.93-0.96). Conclusions: The modified Arabic version of the FCV-19S is a valid and reliable tool to measure fear levels during the pandemic of COVID-19. Using an appropriate psychometric tool to measure the level of fear can help in monitoring changes in population fear levels, and implementing population-level measures to limit unwarranted fear.